E-cigarette devices used by high-school youth. (1st January 2019) - Krishnan-Sarin, Suchitra; Jackson, Asti; Morean, Meghan; Kong, Grace; Bold, Krysten W.; Camenga, Deepa R.; Cavallo, Dana A.; Simon, Patricia; Wu, Ran
Highlights: Among youth, use of JUUL, mods, and vape/hookah pens were higher than cig-a-likes. Nicotine use was highest for JUUL, followed by mods, cig-a-likes, and vape pens. Use of multiple devices was common, but JUUL was the highest single use device. Users of all devices, except JUUL, used other tobacco products. Use of JUUL was associated with higher SES. Abstract: Background E-cigarette use rates are high among youth, but there is limited information on the types of e-cigarette devices that are used by youth. Methods During Spring 2017, students from 4 high schools completed surveys on use of e-cigarette devices (cig-a-like, vape/hookah pen, modified devices or mods, and JUUL). Among youth who endorsed ever (lifetime) use of an e-cigarette and of at least one device (n = 875), we assessed 1) prevalence rates of ever and current (past-month) use of each device, 2) use of nicotine in each device, and 3) predictors [age, sex, race, socioeconomic status (SES), other tobacco use] of ever use of each device and of use of single versus multiple devices. Results Cig-a-likes were used least frequently (Ever use: cig-a-likes: 25.4%; vape/hookah pens: 60.6%; JUUL: 64.2%; mods: 71.2%; Current use: cig-a-likes: 7.3%; vape/hookah pens; 18.7%; mods: 33.1%; JUUL: 47.1%;). Nicotine use was highest for JUUL (JUUL: 80.3%; mods: 56.3%; cig-a-likes: 51.4%; vape/hookah pens: 46.8%). Among ever users of single devices, use of JUUL was highest (JUUL: 43%; mods: 32%; vape/hookah pens: 21%; cig-a-likes: 4%). Ever use of all devices, except JUUL, was associated with other tobacco product use. Ever use of JUUL was associated with higher SES. Ever use of multiple devices (two: 34.7%; three: 25.8%; four: 11.7%) compared with a single device (27.8%) was associated with other tobacco product use. Conclusions Targeted regulatory and prevention efforts that consider the use of multiple e-cigarette devices are needed to lower youth e-cigarette use rates.